How is nature possible? : Kant's project in the First critique - Robinson, Daniel N., 1937- (Continuum, 2012)
How is Nature Possible?: Kant's Project in the First Critique presents a clear and systematic appraisal of what is perhaps the most difficult treatise in the philosophical canon. Daniel N. Robinson situates Kant's undertaking in the First Critique within the context of the history of philosophy and as a response to the challenges of scepticism. Kant's central task in the First Critique is to tie his metaphysical analysis to the very possibility of nature itself. Where others assumed the validity or the weakness of perception and reason, Kant presents a critical appraisal of both, thereby establishing the very limits of sense and reason as instruments of discovery. Ideal for students at all levels, this fascinating introduction clarifies the aims and significance of Kant's project, locates its place within the history of philosophy and identifies the strengths and weaknesses reasonably attributed to this most significant contribution to the history of philosophical reflection.